1921 N.D. Laws 173, ch. 97, § 13. - (:unkn) unknown (General Publisher, 1921)
Provided, however, that if the evidence in such case convinces the court that the person convicted of transporting intoxicating liquors in violation of this Act, was in charge of and used any wagon, buggy, automobile, water or aircraft, or other vehicle or conveyance not owned by him, or without permission of the owner, or when such vehicle or conveyance so sued was mortgaged property, or if there be in or upon such conveyance so used or upon any person therein any firearms, or guns, he shall be deemed guilty of a felony, and be punished by imprisonment in the penitentiary not less than six months and not more than five years.
--
Keywords: CARRY; TRANSPORTATION